Arguing for Classical Critical Theory - Rasmussen, David (Filozofija i društvo (Zbornik radova), 2021)
In my view, making the case for a specific interpretation of Critical Theory is problematic. Although the term has a prestigious origin stemming from Horkheimer’s 1937 paper, Traditional and Critical Theory,2 given during his term as Director of the Institute for Social Research at Frankfurt University and generating the enthusiasm of its members, the term and the movement associated would be defined and radically redefined not only by subsequent generations but by its very author. One of the merits of the book under discussion is that even before the first chapter an ‘Interlude’ is presented entitled Arguing for Classical Critical Theory signifying to the reader that Horkheimer got it right when he defined the subject and that it is possible to return to that particular definition after 83 years. This paper challenges Professor Sorensen’s claims for the restoration of classical Critical Theory on three levels: the scientific, the historical and the political level